Contemporary Criminological Issues : Moving Beyond Insecurity and Exclusion - Piche, Justin; Moffette, David, 1981-; Côte-Lussier, Carolyn, 1983- (Book collections on Project MUSE., 2020)
Introduction : challenging criminology, insecurity, and exclusion / Carolyn Côte-Lussier, David Moffette, and Justin Piche -- section 1. Rethinking critical criminology -- Beyond criminal law and methodological nationalism : borderlands, jurisdictional games, and legal intersections / David Moffette and Anna Pratt -- Police museums, the naturalization of colonial conquests, and the legitimation of law enforcement in Canada and France / Matthew Ferguson, Justin Piche, Gwenola Ricordeau, Carolina S. Boe, and Kevin Walby -- Speaking out of turn : cutting through monologues of exclusion and partisanship / Maritza Felices-Luna and Anouk Guine -- section 2. Critical criminology in practice -- Collaborative teaching and learning : the emotional journey of the University of Ottawa's first Walls to Bridges class / Jennifer M. Kilty, Sandra Lehalle, and Rachel Fayter -- Beyond judgment : how parents and professionals negotiate in/exclusion and (in)security among youth who sexually offend / Christine Gervais, Matthew S. Johnston, Serenna Dastouri, Leslie McGowran, and Elisa Romano -- Addressing the overrepresentation of indigenous peoples in the Canadian criminal justice system : is reconciliation a way forward? / Kathryn M. Campbell and Stephanie Wellman -- section 3. Markers of social differentiation and social reaction -- Security governance and racialization in the "War on Terror" / Baljit Nagra and Jeffrey Monaghan -- Unruly women in neoliberal times : still bad, mad, and sluts / Tuulia Law, Brittany Mario, and Chris Bruckert -- On the weighing of protections : "exerting power and doing good" with child sexual abuse legislation / Christopher Greco and Patrice Corriveau -- Disadvantage, crime, and criminal justice / Carolyn Côte-Lussier, Katrin Hohl, and Jean-Denis David -- section 4. Reflections on criminology -- Using criminological evidence to shift policy : from a punishment to a prevention agenda / Irvin Waller, Verónica Martínez, Audrey Monette, and Jeffrey Bradley -- Afterword. Reflections and intentions : critical criminology in Canada / Gillian Balfour (class of '87 and '94).